1992
DOI: 10.1136/adc.67.11.1376
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoscopy in lipoid pneumonia.

Abstract: Patients and methods Children with resistant or recurrent pneumonia presenting over a three year period to Asir Central Hospital, the only tertiary care facility in the region, were studied. All the children were referred to the otolaryngologist by paediatricians. A detailed history including history of feeding of saman was obtained in each case. A chest radiograph was performed before bronchoscopy.Bronchoscopy was carried out by using a Storz ventilating paediatric bronchoscope of the appropriate size. Any se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…The macroscopic appearance of BAL with fat globules on the fluid surface and the cytologic demonstration of lipid-laden macrophages 14 is consistent with the diagnosis of ELP. Kameswaran et al 15 reported a series of 24 cases of lipoid pneumonia in children, 22 of which were diagnosed by rigid bronchoscopy with BAL. Bronchoscopy has the additional advantage of assessment of airway anatomy to rule out other causes of chronic nonresolving pneumonia.…”
mentioning
confidence: 99%
“…The macroscopic appearance of BAL with fat globules on the fluid surface and the cytologic demonstration of lipid-laden macrophages 14 is consistent with the diagnosis of ELP. Kameswaran et al 15 reported a series of 24 cases of lipoid pneumonia in children, 22 of which were diagnosed by rigid bronchoscopy with BAL. Bronchoscopy has the additional advantage of assessment of airway anatomy to rule out other causes of chronic nonresolving pneumonia.…”
mentioning
confidence: 99%
“…Lipid‐laden macrophages are the cytological finding and therefore, invasive methods such as fine‐needle aspiration and open lung biopsy have been advocated 6 . Bronchoscopy with bronchial lavage is considered a reliable and minimally invasive diagnostic method 7 . In the present case, BAL and open lung biopsy were performed and the oil red O stain was positive for exogenous lipid and foamy macrophages in the lung.…”
Section: Discussionmentioning
confidence: 68%
“…These oils were used for three main reasons: (1) cultural (2) medical or (3) behavioural. Ghee (rendered animal fat) and olive oil were commonly documented in studies from Saudi Arabia and India for which they were used culturally for oral/nasal cleansing purposes in oil baths, as a laxative, for nutritional supplements, to prevent coughs and colds and to generally promote good health [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Shark liver oil was mainly reported in South Korea for cultural reasons [23].…”
Section: Oil Use and Rationalementioning
confidence: 99%
“…Corticosteroid use was reported in 20 studies and administered by different routes; intravenous dexamethasone at 0.3 mg/kg was given for two weeks [45], prednisone was administered at 1-2 mg/kg/day from 2 weeks to 14 months [10,18,19,24,28,31,47], and inhaled beclomethasone was given at 250 mcg 12 hourly for 6 months [47]. Therapeutic partial or whole lung lavage [12,24,25,27,39,43,46] and surgical resection were additional treatment modalities reported in children with ELP [7,10,11,22,42,44].…”
Section: Treatment and Clinical-radiological Outcomesmentioning
confidence: 99%